Assessment of the Effects of Organic Fertilizer Applications on the Biochemical Quality of Basil - Ömer Ertürk; Melek Çol Ayvaz; Meltem Ocak; Tuğba Özbucak (Journal of Agricultural Sciences)
It is important to characterize the biochemical potential of medicinal and aromatic plants, which have significant therapeutic and commercial value. However, fertilizers obtained from natural resources are used in sustainable agricultural practices. In this study, basil (Ocimum basilicum L.) was grown from seed with different doses of barnyard manure, vermicompost and chicken manure were added. This work aimed was to investigate and compared the effect of these different fertilizer doses applications on the biochemical potential of basil plants.Total phenolic content, antioxidant capacity and antimicrobial activity values were statistically significant according to the type and doses of fertilizer studied. Linalool was found to be the highest amount of volatile compound in leaf samples of manure treated plants. The highest antioxidant capacity values were determined in the samples where farm manure and chicken manure were applied at low (2.5%) and medium (20%) doses and worm manure was applied at high doses. The highest antibacterial effect was detected in the essential oil extract of leaf samples with 10% vermicompost against Bacillus cereus. Among the Gram (-) bacteria, the highest antibacterial effect against E. coli was determined in the essential oil extract of leaf samples with 20% farm manure. The essential oil extract of leaf samples with 20% farm manure also showed significant and high degree of antifungal effect against S. cerevisae.